Comparison of in-season-specific resistance vs. a regular throwing training program on throwing velocity, anthropometry, and power performance in elite handball players - Hermassi, S.; van den Tillaar, R.; Khlifa, R.; Chelly, M. S.; Chamari, K. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this study was to compare the effect of a specific resistance training program (throwing movement with a medicine ball) with that of regular training (throwing with regular balls) on ball velocity, anthropometry, maximal upper-body strength, and power. Thirty-four elite male team handball players (age: 18 ± 0.5 years, body mass: 80.6 ± 5.5 kg, height: 1.80 ± 5.1 m, body fat: 13.4 ± 0.6%) were randomly assigned to 1 of the 3 groups: control (n = 10), resistance training group (n = 12), or regular throwing training group (n = 12). Over the 8-week in season, the athletes performed 3 times per week according to an assigned training program alongside their normal team handball training. One repetition maximum (1RM) bench press and 1RM pullover scores assessed maximal arm strength. Anthropometry was assessed by body mass, fat percentage, and muscle volumes of upper body. Handball throwing velocity was measured by a standing throw, a throw with run, and a jump throw. Power was measured by measuring total distance thrown by a 3-kg medicine ball overhead throw. Throwing ball velocity, maximal strength, power, and muscle volume increases for the specific resistance training group after the 8 weeks of training, whereas only maximal strength, muscle volume and power and in the jump throw increases were found for the regular throwing training group. No significant changes for the control group were found. The current findings suggest that elite male handball players can improve ball velocity, anthropometrics, maximal upper-body strength, and power during the competition season by implementing a medicine ball throwing program